2021
DOI: 10.1186/s13071-020-04563-8
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance status of malaria vectors Anopheles gambiae (s.l.) of southwest Burkina Faso and residual efficacy of indoor residual spraying with microencapsulated pirimiphos-methyl insecticide

Abstract: Background The rapid spread of insecticide resistance in malaria vectors and the rebound in malaria cases observed recently in some endemic areas underscore the urgent need to evaluate and deploy new effective control interventions. A randomized control trial (RCT) was conducted with the aim to investigate the benefit of deploying complementary strategies, including indoor residual spraying (IRS) with pirimiphos-methyl in addition to long-lasting insecticidal nets (LLINs) in Diébougou, southwes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…Mortality rates of 98-100% indicate susceptibility, 90-97% indicate a candidate for resistance (further investigation is needed), and less than 90% indicate resistance(76), as shown in Table-3. Previous ndings from Burkina Faso, Uganda, Mali, Rwanda, Kenya, and Tanzania agree with this one from 2005 to 2017 (16, 34,36,37,[54][55][56][57].…”
Section: Discussionsupporting
confidence: 73%
“…Mortality rates of 98-100% indicate susceptibility, 90-97% indicate a candidate for resistance (further investigation is needed), and less than 90% indicate resistance(76), as shown in Table-3. Previous ndings from Burkina Faso, Uganda, Mali, Rwanda, Kenya, and Tanzania agree with this one from 2005 to 2017 (16, 34,36,37,[54][55][56][57].…”
Section: Discussionsupporting
confidence: 73%
“…populations to insecticides in several regions in Burkina Faso ( Dabiré et al, 2008 ; Namountougou et al, 2012 ). These resistances are thought to be due to the pressure of insecticides used against adult mosquitoes in households (LLINs, IRS), to the pressure exerted on larvae in breeding sites contaminated by insecticides used in agriculture, to the use of repellents in homes ( Soma et al, 2021 ). In addition, antimalarial drug resistance in Plasmodium spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, the emergence of resistance to the main classes of insecticides used in the treatment of bed nets and in indoor residual spraying (IRS) requires re-thinking the use of these tools and the management of resistance in vectors [2]. Resistance has already been reported in various West African countries including Benin, Burkina Faso, Mali [3][4][5] and particularly in Togo [6,7]. Recent studies showed that the use of synergists and combination of insecticide formulations can increase the susceptibility of malaria vectors in areas with high pyrethroid resistance [8,9].…”
Section: Introductionmentioning
confidence: 99%